Effect of storage on physical and functional properties of extracellular vesicles derived from neutrophilic granulocytes - Ákos M. Lőrincz; Csaba I. Timár; Krisztina A. Marosvári; Dániel S. Veres; Lilla Otrokocsi; Ágnes Kittel; Erzsébet Ligeti (Journal of Extracellular Vesicles, 2014)
Aim: To carry out a systematic study on the effect of different storage conditions on the number as well as the physical and functional properties of antibacterial extracellular vesicles (EVs) derived from human neutrophilic granulocytes. Methods: Production of EVs with antibacterial properties was initiated by opsonized Zymosan A particles. The number of released fluorescent EVs was determined by flow cytometry following careful calibration. Physical properties and size of EVs were investigated by flow cytometry, dynamic light scattering and electron microscopy. Functional properties of EVs were tested by bacterial survival assay. Results: Storage at +20°C or +4°C resulted in a significant decrease of EV number and antibacterial effect after 1 day. Storage at −20°C did not influence the EV number up to 28 days, but induced a shift in EV size and almost complete loss of antibacterial function by 28 days. Storage at −80°C had no significant effect either on EV number or size and allowed partial preservation of the antibacterial function up to 28 days. Snap-freezing did not improve the results, whereas the widely used cryoprotectants induced EV lysis. Conclusion: Storage significantly alters both the physical and functional properties of EVs even if the number of EVs stays constant. If storage is needed, EVs should be kept at −80°C, preferably not longer than 7 days. For functional tests, freshly prepared EVs are recommended.